Application of ecosystem-specific reference databases for increased taxonomic resolution in soil microbial profiling - Overgaard, Christina Karmisholt; Tao, Ke; Zhang, Sha; Christensen, Bent Tolstrup; Blahovska, Zuzana; Radutoiu, Simona; Kelly, Simon; Dueholm, Morten Kam Dahl (Frontiers in Microbiology, 2022)
Intensive agriculture systems have paved the way for a growing human population. However, the abundant use of mineral fertilizers and pesticides may negatively impact nutrient cycles and biodiversity. One potential alternative is to harness beneficial relationships between plants and plant-associated rhizobacteria to increase nutrient-use efficiency and provide pathogen resistance. Plant-associated microbiota profiling can be achieved using high-throughput 16S rRNA gene amplicon sequencing. However, interrogation of this data is limited by confident taxonomic classifications at high taxonomic resolution (genus- or species-level) with the commonly applied universal reference databases. High-throughput full-length 16S rRNA gene sequencing combined with automated taxonomy assignment (AutoTax) can be used to create amplicon sequence variant resolved ecosystems-specific reference databases that are superior to the traditional universal reference databases. This approach was used here to create a custom reference database for bacteria and archaea based on 987,353 full-length 16S rRNA genes from Askov and Cologne soils. We evaluated the performance of the database using short-read amplicon data and found that it resulted in increased genus- and species-level classification compared to commonly used universal reference databases. The custom database was utilized to evaluate the ecosystem-specific primer bias and taxonomic resolution of amplicon primers targeting the V5-V7 region of the 16S rRNA gene commonly used within the plant microbiome field. Finally, we demonstrate the benefits of custom ecosystem-specific databases through the analysis of V5-V7 amplicon data to identify new plant-associated microbes for two legume and two cereal species.